2012
DOI: 10.1073/pnas.1117982109
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning and characterization reveal the molecular basis for soybean maturity locus E1 that regulates photoperiodic flowering

Abstract: The complex and coordinated regulation of flowering has high ecological and agricultural significance. The maturity locus E1 has a large impact on flowering time in soybean, but the molecular basis for the E1 locus is largely unknown. Through positional cloning, we delimited the E1 locus to a 17.4-kb region containing an intron-free gene (E1). The E1 protein contains a putative bipartite nuclear localization signal and a region distantly related to B3 domain. In the recessive allele, a nonsynonymous substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
551
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 390 publications
(633 citation statements)
references
References 79 publications
21
551
0
14
Order By: Relevance
“…We identified some local differentiation signals that have not been detected previously in the screening of domestication and improvement selection, such as the E1 gene, which is responsible for the major flowering time (FT) QTL 29,30 . Typically, soybeans in northern regions have shorter maturity periods, whereas those in southern regions have longer maturity periods 31 .…”
Section: Local Breeding and Related Traitsmentioning
confidence: 97%
“…We identified some local differentiation signals that have not been detected previously in the screening of domestication and improvement selection, such as the E1 gene, which is responsible for the major flowering time (FT) QTL 29,30 . Typically, soybeans in northern regions have shorter maturity periods, whereas those in southern regions have longer maturity periods 31 .…”
Section: Local Breeding and Related Traitsmentioning
confidence: 97%
“…The dysfunction of e4 allele in Miharudaizu is caused by an insertion of a Ty1/copia-like retrotransposon, SORE-1, in exon 1 [17]. An analysis with allele-specific Aomori L145 (6) Sakamotowase (15) Kosodefuri (9) Yoshiokachuryu (11) Pando (14) Aomori L146 (19) (27) GL1738 (13) GL2216 (12) Keshuang (25) 0.05 markers, which detect the presence or absence of the insertion, however, revealed that Kamaishi-17 did not have the e4 allele in which SORE-1 had been inserted [22]. This prompted us to analyze the E4 (GmphyA2) sequences of Kamaishi-17 and the other photoperiod-insensitive accessions.…”
Section: Sequence and Dna Marker Analyses Of E4mentioning
confidence: 99%
“…Group II consisted of landraces that are grown as a short-season crop across Japan and the Korean peninsula (9-15), including Sakamotowase, which has the genotype e3e3E4E4 and a dysfunctional allele (e1-fs) at the E1 locus [19][20][21]. Group III consisted of landraces collected in northern Honshu, Japan (16)(17)(18)(19)(20)(21). Tsukue-4 (group IV, accession 22) and Otomewase (group V, accession 23) together formed a loose clade.…”
Section: Classification Of Photoperiod-insensitive Soybean Accessionsmentioning
confidence: 99%
See 2 more Smart Citations